Korelasi Tingkat Kepercayaan Diri Terhadap Prestasi Belajar Mahasiswa di IAIN Syekh Nurjati Cirebon (Studi Pada Calon Pendidik Matematika) - Uun Badriyah; Widodo Winarso (Jurnal Pendidikan Matematika, 2018)
The success of education is reflected in the quality of high achieving graduates. There are many factors that influence student achievement of Tadris Matematika IAIN Sheikh Nurjati Cirebon as a candidate educator one of them is confidence attitude. Confidence is a form of readiness as an educator. On the basis of this researcher conducted research with descriptive correlational research method. Data collection instruments used were questionnaires, study documentation, and observation. The result of the research is the mean of the confidence level of students of Mathematics education IAIN Syekh Nurjati Cirebon is 69,36% it means student self-confidence level is high. The average achievement of student achievement of Mathematics IAIN Syekh Nurjati Cirebon is 3.32 shows the mean that the average achievement of students majoring in Mathematics education IAIN Syekh Nurjati Cirebon quite good. Based on Product Moment correlation test obtained a value of positive significance or equal to 67.7% means that there is a correlation between self-confidence in learning mathematics with the achievement of student learning Mathematics IAIN Syekh Nurjati Cirebon. Students 'self-confidence level on learning presentation shows the higher the students' self-confidence the better the student's achievement of Mathematics